SURVEY AND ROAD MEASUREMENT TECHNIQUES IN POJA VILLAGE, SAPE SUB-DISTRICT.: Survey, Measurement, Road Terrain Slope - B. Erdiansyah Putra; Muh. Apriansyah; St Zulaiha Nurhajarurahmah; Fathurrahman; Ananda Galang Wangsa5 (Journal of Excellence Humanities and Religiosity, 2024)
The development of road access is currently a very important thing in infrastructure development in a country. Good road access can facilitate community mobility and support economic growth. Currently, the government is trying to improve road access in every region and village through the construction of new roads, repairing existing roads. The implementation method of measuring new roads is an important process in infrastructure development. This method involves the use of specialized equipment such as distance measuring devices and angle measuring devices. The purpose of this service activity is to determine the length, width, elevation and slope of the new road terrain. The location of the activity is Poja Village, Sape District, Bima Regency, West Nusa Tenggara. The results of the road terrain slope analysis on the Poja Village road section, Sape District, Bima Regency, were calculated at each STA with a distance of 500 meters for each STA. Obtained road terrain slope STA 00+000 - STA 00+500 is 0.2%, STA 00+0500 - STA 01+000 is 0.8%, STA 01+000 - STA 01+500 is 0.4%, STA 01+500 - STA 02+000 is 0.6, STA 02+00 - STA 02+500 is 1.8%, STA 02+500 - STA 03+00 is 1.2%. And the road section of Poja Village, Sape District, Bima Regency is included in the Flat (D) road terrain category, because all segments every 500 meters have a value smaller than 3%.